Análise das condições de desempenho e acessibilidade no reuso de contêineres para fins de comércio e serviços - Bueno, Camila Aparecida Pires (2019)
Container reuse can be a sustainable construction alternative compared to traditional construction methods because it reduces the use of natural raw materials and the production of waste and disposal. It is important to highlight that, although marine containers seem to be a sustainable and inexpensive alternative for homes, offices and commercial establishments, some adaptations must be designed and made so that this element becomes habitable and offers user comfort. To date, there are no specific standards and studies on the performance and accessibility of container use, thus being a gap in the construction literature. The term sustainability is recurrent, but buildings often do not meet minimum housing requirements. Given this scenario, we saw the need for further study about this building model, which was made through analyzes of different buildings. In this context, the objective of this work was to perform an analysis of the performance and accessibility conditions in the reuse of containers in commercial and service establishments, through questionnaires applied to users. The questionnaire was based on current performance and sustainability standards. From the compilation of data, the results of the analysis were obtained for each requirement and establishments studied, identifying which guidelines fit the standards of performance and accessibility. The best result for the Safety requirement and the worst result for the Thermal Performance was verified. Finally, it was noted the importance of a checklist for checking the most important requirements applied to the types studied and thus establishing a continuous improvement of performance and accessibility for the reuse of containers in construction.